2001
DOI: 10.1259/bjr.74.878.740186
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular haemophilic pseudotumour containing a fluid–fluid level

Abstract: Osseous haemophilic pseudotumours are uncommon. Mandibular haemophilic pseudotumours are rare, with only approximately 12 cases reported in the literature to date. We present imaging findings of a histopathologically proven mandibular haemophilic pseudotumour. A fluid-fluid level, hitherto not associated with this condition, is also described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Other patterns of imaging features including an extensive fine trabecular bone pattern, 12 spicules perpendicular to a lesion, 13 fluid-fluid level in an osteolytic lesion 19 and periosteal strut from the cortex into a soft-tissue mass, 4,8 only new bone formation without an osteolytic portion 6 and flecks of calcification inside the lesion 1,22 have also been described in the previous reports.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Other patterns of imaging features including an extensive fine trabecular bone pattern, 12 spicules perpendicular to a lesion, 13 fluid-fluid level in an osteolytic lesion 19 and periosteal strut from the cortex into a soft-tissue mass, 4,8 only new bone formation without an osteolytic portion 6 and flecks of calcification inside the lesion 1,22 have also been described in the previous reports.…”
Section: Discussionmentioning
confidence: 64%
“…In this report, we briefly summarized our case and the previous 24 studies, 1,[3][4][5][6][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] which included 32 cases, on haemophilic pseudotumours of the jaw. Table 1 shows the summary of studies conducted between 1968 and 2014, including the present case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intra muscular pseudotumours may be seen in areas of greater mobility and more prone to minor trauma such as the major flexors of the limbs, the calf, and forearm flexors. Our review of literature suggested that pseudotumours of the mandible or maxilla, occurred in young patients rather than in adults [2,3,[7][8][9][10]. It has only been described in the dentate region of the mandible and not elsewhere.…”
Section: Discussionmentioning
confidence: 83%
“…As a valuable imaging feature, fluid-fluid levels have been described in aneurysmal bone cysts, giant cell tumour and so on. The sign occurring in Cases 2 and 3 may represent different layers secondary to repeated bleeding into the cystic cavity [15]. CT and MRI are also useful in the follow-up for patients after surgery, as well as in monitoring the treatment response.…”
Section: Discussionmentioning
confidence: 99%